Pengaruh Servant Leadership dan Budaya Organisasi Terhadap Kinerja Guru Sekolah Baptis Palembang - Christiani, Lia (Yayasan Sembilan Pemuda Indonesia, 2025)
This research aims to analyze the influence of servant leadership and organizational culture on teacher performance in Baptist schools in Palembang. The research sample involved teachers from all units in Baptist Schools in Palembang as research respondents. The research method used was quantitative with a survey approach. Data were collected through questionnaires which were then analyzed using multiple linear regression analysis. The results of the research show that both servant leadership and organizational culture significantly influence teacher performance. Effective servant leadership and a positive organizational culture can increase teacher motivation, job satisfaction, and productivity, thereby impacting overall performance improvement.